2011
DOI: 10.1590/s2179-64912011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Da suspeita à intervenção em surdez: caracterização deste processo na região de Campinas/SP

Abstract: From suspicion to intervention in deafness: characterization of this process in Campinas/SP Da suspeita à intervenção em surdez: caracterização deste processo na região de Campinas/SP ABSTRACT Purpose: To identify and detail the current situation of diagnosis and assistance to deaf children in two cities belonging to the administrative region of Campinas (SP). Methods: It was conducted a survey of 320 medical records of patients diagnosed with prelingual deafness in the period between 1996 and 2005, in two ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 10 publications
3
12
1
9
Order By: Relevance
“…The increased duration of the diagnostic step can be related to the greater number of audiological tests required for completion of diagnosis in these children. 24 In this study, regardless of the degree of hearing loss, age at diagnosis and ISAD fitting occurred late, which is in disagreement with what is proposed in the literature, i.e., that the auditory diagnosis should be established before the third month of life and speech therapy intervention be started by 6 months of age. 1,22,25 Some studies carried out in Brazil also showed that it was difficult to achieve the recommended standards.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The increased duration of the diagnostic step can be related to the greater number of audiological tests required for completion of diagnosis in these children. 24 In this study, regardless of the degree of hearing loss, age at diagnosis and ISAD fitting occurred late, which is in disagreement with what is proposed in the literature, i.e., that the auditory diagnosis should be established before the third month of life and speech therapy intervention be started by 6 months of age. 1,22,25 Some studies carried out in Brazil also showed that it was difficult to achieve the recommended standards.…”
Section: Discussioncontrasting
confidence: 89%
“…In a study that assessed the status of the diagnosis and care of patients with hearing loss aged 0---14 years in the city of Campinas, the mean age at diagnosis was 4.3 years and the mean age at ISAD fitting was 7.5 years. 24 In the study that aimed to characterize the age at diagnosis and intervention of children treated at the Hospital das Clínicas de São Paulo, the mean age at these steps was 5.4 years and 6.8 years, respectively. 6 These aspects of language intervention become relevant because the age at diagnosis and adaptation are determining factors for the prognosis of auditory and language skill development in children with hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that identification of HL occur within the first three months of life, so that intervention measures can be adopted before six months of age (8) . Nevertheless, some studies (22)(23) have described that the time between the suspicion of auditory alteration and its confirmation can reach 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…Some factors may contribute to this monitoring, bringing improvements to the effectiveness of the child hearing health programme, such as investment in guidance to families about the importance of listening to language development, to improve their adherence to audiological monitoring and consequently provide the diagnosis of possible hearing loss 1,4,8 . In certain cases, even without the presence of risk indicators, the family should return to the programme after hearing screening for other hearing tests of the child in order to complete the diagnosis.…”
Section: Methodsmentioning
confidence: 99%